Conflict Management Strategies, A Panacea for Effective Educational Leadership - Tamunodiepiriye, Iyaye Peace; Bedzra, Linda; Essuman, Joana (Gyan Management Journal, 2022)
Humans constitute the organization’s human resources; hence conflict is inevitable in every organisation with people. Conflict is a word with both good and bad connotations. When conflict is poorly managed or handled, a crisis will ensue. Consequently, the purpose of this article was to investigate conflict management in school organisations in Ghana and Nigeria. It determined the causes and sources of organisational disputes. It also explored the many conflict management tactics available to school administrators, including behaviour management, negotiation, and mediation, among others. This paper also emphasised the effects of unmanaged conflict in the educational system. This is an opinion piece, as it argues that educational leaders should share available resources evenly and hold seminars, conferences, and symposia on ways to manage conflict. Originality/value: A novel approach for understanding the brand gamification concept on 6thinking hats approach is presented in the study. This article provides a base for future studies from an empirical angle in this domain that has not been taken up in this particular study. Limitations: This paper used qualitative study and the quantitative study has not been addressed in this article.